Hubungan Kelengkapan Informasi Penunjang Dengan Keakuratan Kode Diagnosis Pneumonia Pada Rekam Medis Pasien Rawat Inap Di Rumah Sakit dr. Soedono Madiun - Nina Asih Sulistyaningrum; Sri Sugiarsi; Sri Mulyono (Indonesian Journal of Health Information Management, 2026)
In determining the diagnosis code, supporting information is needed, because the more complete the supporting information, the more accurate and precise the resulting code will be. Based on a preliminary study of 10 medical records of inpatients diagnosed with pneumonia at dr. Soedono Madiun shows a rate of incomplete supporting information of 30% and inaccuracy of 20%. The aim of the study was to determine the relationship between the completeness of supporting information and the accuracy of the pneumonia diagnosis code in the medical records of inpatients at dr. Soedono Madison. The research design used was analytic observational. The population in this study were 350 medical records of inpatients diagnosed with pneumonia. The sample size is 66 medical records. The sampling technique uses simple random sampling and is assisted by Excel using the rand and rank functions. The research instrument uses observation guidelines. Data processing techniques by collecting, editing, coding, entering, processing, and cleaning. Univariate and bivariate data analysis. The statistical test used is the Fisher Exact Test. The results of the completeness of the supporting information were 47 (71,2%) complete, 19 (28,8%) incomplete, and the accuracy of the pneumonia diagnosis code was 59 (89,4%), 7 (10,6%) inaccurate. In conclusion, there is a relationship between the completeness of supporting information and the accuracy of the pneumonia diagnosis code in the medical records of inpatients at Dr. Soedono Madiun with a value of p = 0,001.